Web crippling of cold-formed ferritic stainless steel square and rectangular hollow sections. (1st December 2018) - Li, Hai-Ting; Young, Ben
Highlights: Cold-formed ferritic stainless steel hollow sections undergoing web crippling were investigated. A total of 44 tests was carried out under EOF, IOF, ETF, and ITF loading conditions. Finite element models were developed and validated against the test results. A parametric study of 154 specimens for both slender and stocky sections was performed. Existing web crippling design provisions are assessed and improved design rules are proposed. Abstract: This paper presents experimental and numerical investigations on cold-formed ferritic stainless steel (CFFSS) square and rectangular hollow sections undergoing web crippling. A total of 44 web crippling tests was carried out under the four codified web crippling load cases as per the American cold-formed stainless steel specification. Numerical model of each load case was built and verified with the web crippling test results. After the verification, a parametric study comprised of 154 finite element analyses was undertaken thereafter to gain further insight into the behaviour of the CFFSS sections undergoing web crippling. The current design provisions in the American, Australian/New Zealand and European stainless steel codes of practice were assessed. Moreover, the North American Specification (NAS) provisions for carbon and low-alloy steel sections were evaluated. Furthermore, design recommendations in the literature for stainless steel sections were examined. Improved design rules are proposed in this study for CFFSS square and rectangular hollow sections by modifying NAS and Direct Strength Method. Reliability analysis was also undertaken to assess the reliability levels of the existing and modified provisions.